2016
DOI: 10.1177/2165143416651717
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Mentoring and Persistence in STEM for Students With Disabilities

Abstract: The purpose of this study was to investigate the effectiveness of virtual mentoring for enhancing the persistence of secondary and postsecondary students with disabilities engaged in science, technology, engineering, and mathematics (STEM) learning. The student participants ( N = 189) were all engaged in STEM coursework and enrolled in a virtual-mentoring program for a span of 4 years. Persistence was measured with an online survey designed to evaluate growth across self-determination, self-advocacy, STEM aspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 23 publications
2
40
0
3
Order By: Relevance
“…In a recent research study conducted by Gregg et al, (2016) their team investigated the effectiveness of using virtual mentoring to enhance persistence essential for secondary and post secondary students with disability enrolled in STEM learning (Gregg et al, 2016). Their evidence showed positive results using intentional frameworks and constructs to help enhance persistence and engagement.…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent research study conducted by Gregg et al, (2016) their team investigated the effectiveness of using virtual mentoring to enhance persistence essential for secondary and post secondary students with disability enrolled in STEM learning (Gregg et al, 2016). Their evidence showed positive results using intentional frameworks and constructs to help enhance persistence and engagement.…”
Section: Modelmentioning
confidence: 99%
“…Their evidence showed positive results using intentional frameworks and constructs to help enhance persistence and engagement. Their Research uncovered findings from the National Science Foundation that indicated that 1 out of 4 students with a disability enroll in a STEM major (Gregg et al, 2016). In addition, 56% of students with a disability do not report that they have a learning disability (Newman, et al, 2010).…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Por otro lado, existe una terminología variada en torno a la idea de mentoría a distancia, a saber: e-mentoría, mentoría online, mentoría virtual, tele-mentoría etc. La característica principal de esta modalidad de mentoría radica en que la relación entre el mentor y el mentorizado (estudiante novel, también denominado mentee o telémaco) se realiza mediante las nuevas tecnologías como canal de comunicación principal (Gregg, Wolfe, Jones, Todd, Moon, y Langston, 2016;Haran y Jeyaraj, 2019;Alhadlaq, Kharrufa y Olivier, 2019). Entre los beneficios de esta modalidad de mentoría destaca su flexibilidad espacio temporal, ya que su carácter asincrónico permite a las personas mentoras poder elaborar más profundamente sus respuestas, facilitando la comunicación en el caso de personas más tímidas, además de la posibilidad de poder llegar a más personas (Rísquez y Sánchez-García, 2012;Grace, Raghavendra, McMillan, y Gunson, 2019).…”
Section: Introductionunclassified